Controlling Raw Material Inventory using the Economic Order Quantity (EOQ) Method at PT. ICI Paints Indonesia - Sutejo, Mohamad Bambang; Suprayitno, Degdo; Latunreng, Wahyuddin (Yayasan Sinergi Kawula Muda, 2023)
The inventory control system comprises a set of control policies to determine the level of inventory to be maintained, when orders to replenish inventory should be placed, and how large orders should be. This system determines and ensures the availability of inventory in the right quantity and at the right time. The aim of inventory is in the right quantity and at the right time. Inventory management aims to provide the necessary raw materials for the production process to run smoothly without shortages or excess inventory, thus minimizing inventory control of raw materials, specifically Titanium Dioxide and Calcium Carbonate. The company often faces shortages and excess inventory of these raw materials. The company must estimate the future demand for Titanium Dioxide and Calcium Carbonate raw materials. This prompts the research question of how to analyze the implementation of the Economic Order Quantity (EOQ) method for inventory control of these specific raw materials at PT. ICI Paints Indonesia. This research employs qualitative techniques and analyzes data using the Economic Order Quantity (EOQ) method, Lead Time, Re-Order Point, and Total Inventory Cost Order. The results of this study indicate that inventory control of raw materials using the Economic Order Quantity (EOQ) method is more efficient for managing Titanium Dioxide and Calcium Carbonate raw materials at PT. ICI Paints Indonesia. The company can optimize the inventory of Titanium Dioxide and Calcium Carbonate raw materials and reduce purchasing costs. By establishing a reorder point, the company can anticipate excess or shortage of Titanium Dioxide and Calcium Carbonate raw materials, thus minimizing inventory-purchasing costs.